A KEY LESSON FROM FRANCES HESSELBEIN THAT TRANSFORMED MY APPROACH TO LIFE AND LEADERSHIP - Caprino, Kathy (Leader to leader, 2023)
The author, an international career and leadership coach, writer, speaker, and executive trainer, recounts her interview with Frances Hesselbein that appeared in her Forbes blog “Career Bliss.” Among Hesselbein’s quotes from the interview: “A great leader does not preach about their values; they live them. In the end, it is the quality and character of a leader that determines their performance and results.” The author writes that in “13 years of interviewing hundreds of top leadership and business experts, entrepreneurial gurus, writers, artists and others,” she discovered that they “chose to embark on identifying what they value most as a human being ‐ and who they wanted to be in the world – and became the living embodiment of that, for the betterment of themselves and others.”